2002
DOI: 10.1121/1.1492821
|View full text |Cite
|
Sign up to set email alerts
|

The propagation of sound in narrow street canyons

Abstract: This paper addresses an important problem of predicting sound propagation in narrow street canyons with width less than 10 m, which are commonly found in a built-up urban district. Major noise sources are, for example, air conditioners installed on building facades and powered mechanical equipment for repair and construction work. Interference effects due to multiple reflections from building facades and ground surfaces are important contributions in these complex environments. Although the studies of sound tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…In practice, some energy incident on the walls is absorbed, and the simplest way of including this in the ray model (cf. [1,4]) is to introduce an absorption coefficient a 2 ½0,1, such that the magnitude I of the intensity along a ray undergoing a reflection at the boundary is attenuated according to the rule…”
Section: Ray Theory and Energy Propagationmentioning
confidence: 99%
“…In practice, some energy incident on the walls is absorbed, and the simplest way of including this in the ray model (cf. [1,4]) is to introduce an absorption coefficient a 2 ½0,1, such that the magnitude I of the intensity along a ray undergoing a reflection at the boundary is attenuated according to the rule…”
Section: Ray Theory and Energy Propagationmentioning
confidence: 99%
“…Recently, Li and Iu presented a ''coherent'' model, or the complex image source model, for the prediction of sound propagation in street canyons, 9 long enclosures 10 and tunnels. 11 The model was based on an analytic Green's function, which allowed a variation of the reflection factors with the angle of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Picaut et al presented the results of a successful measurement campaign in a single street canyon [16]. Also, scale model measurements have been conducted to show the usefulness of the developed models [10,16,17,18,19]. In contrast to street canyon situations, studies on squares are more rare.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the assumption of diffuse reflections, the diffusion equation [8] and a radiosity based model were presented [9]. For narrow street canyons, Iu and Li showed that a coherent image sources model is necessary rather than an energy based model [10]. Other valuable contributions to modelling sound propagation in a street canyon can be found in references [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%